2010
DOI: 10.1007/s10509-010-0541-5
|View full text |Cite
|
Sign up to set email alerts
|

A family of well behaved charge analogues of a well behaved neutral solution in general relativity

Abstract: A family of charge analogues of a neutral solution with g 44 = (1 + Cr 2 ) 6 has been obtained by using a specific electric intensity, which involves a parameter K. Both neutral and charged solutions are analysed physically subject to the surface density 2 × 10 14 gm/cm 3 (neutron star). The neutral solution is well behaved for 0.0 < Ca 2 ≤ 0.10477 while its charge analogues are well behaved for a wide range of a parameter K (0 ≤ K ≤ 72) i.e. pressure, density, pressuredensity ratio, velocity of sound is monot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…Pant et al [6] shown that a charged solution possess positively finite pressure and density at the center which fulfill the casuality condition, i.e., d P r dρ ≤ 1. Maurya and Gupta [7,8] derived a e-mail: ayishanasim2@gmail.com b e-mail: azam.math@ue.edu.pk charged solutions with metric potential g 44 = B(1 + Cr 2 ) n for every integral value of n, by specifying electric field intensity in terms of parameter K and remarked that all solutions for n ≥ 4 are well behaved for some range of parameter K.…”
Section: Introductionmentioning
confidence: 99%
“…Pant et al [6] shown that a charged solution possess positively finite pressure and density at the center which fulfill the casuality condition, i.e., d P r dρ ≤ 1. Maurya and Gupta [7,8] derived a e-mail: ayishanasim2@gmail.com b e-mail: azam.math@ue.edu.pk charged solutions with metric potential g 44 = B(1 + Cr 2 ) n for every integral value of n, by specifying electric field intensity in terms of parameter K and remarked that all solutions for n ≥ 4 are well behaved for some range of parameter K.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several such metrics have been produced, but only the metric of Kuchowicz (1967) electrified in Gupta and Maurya (2011c), the Durgapal IV metric (1982) electrified in Pant (2011b), the Durgapal V metric (1982) electrified in Gupta and Maurya (2011b), and the two metrics of Pant (2011a) electrified in Maurya and Gupta (2011a) and Pant and Rajasekhara (2011) have been shown to satisfy all the above-mentioned physical constraints in the limit as Q → 0 (see Table 1). In these five electrified metrics, the coefficient of dt 2 (i.e., g tt in ds 2 = g tt dt 2 + g rr dr 2 + r 2 d 2 ) is by construction the same as in the chargeless case.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, Many of the authors obtained the parametric class of exact solutions of Einstein-Maxwell field equations by electrifying some well known uncharged fluid spheres e.g. Tolman (1939) solution by Cataldo and Mitskievic (1992), Heintzmann's (1969) solution by Pant et al (2010), Durgapal V (1982) by Gupta and Maurya (2010), Durgapal IV (1982) by Pant (2010b), Pant I solution (2010a) by Maurya and Gupta (2010a), etc. These coupled solutions are well behaved with some positive values of charge parameter K and completely describe interior of the super-dense astrophysical objects with charge matter.…”
Section: Introductionmentioning
confidence: 99%